Polymeric Optical Splitter Based on Multimode Interference Mechanism - Ibrahim, Mohd. Haniff (Institute of Electrical and Electronics Engineers (IEEE), 2006)
A 1x2 and 1x3 planar optical splitter based on BenzoCyclobutene (BCB 4024-40) polymeric material is proposed. The device is designed based on symmetric interference mechanism, utilizing a BK7 glass as a substrate and thin layer of SiO2 as a cover. Simulation results show that the splitting uniformity is better than 0.5 dB at 1550 nm optical wavelength.